OPTIMALISASI ASESMEN UNTUK SEKOLAH MENENGAH KEJURUAN PADA KURIKULUM MERDEKA - Sri Murwantini (Steam Engineering, 2023)
This research aims to study the optimization of assessments for vocational high schools (SMK) in the Kurikulum Merdeka. The assessment in the Kurikulum Merdeka includes formative and summative assessments In SMK there is a form of assessment or assessment that distinguishes it from other levels, namely: fieldwork practice assessment, Vocational competency test and Competency Unit Examination. Optimization of assessments is done by making good assessment planning including the formation of assessment objectives, formulation of achievement criteria, selection of appropriate assessment instruments and applying high order thinking skills (HOTS). Assessment planning must be clearly illustrated in the RPP or Teaching Module developed, as well as the implementation of the assessment according to planning in the learning process.